Comorbid Pathology in Clinical Trial Participants: Autopsy Findings and Clinical Features. (20th December 2022) - Jicha, Gregory A; Barber, Justin M; Abner, Erin L; Gold, Brian T.; Kryscio, Richard J; Schmitt, Frederick A.; Van Eldik, Linda J; Wilcock, Donna M; Nelson, Peter T
Abstract: Background: The presence of multiple comorbid pathologic features in late onset dementia has been well documented across cohort studies that incorporate autopsy evaluation. It is likely that such mixed pathology may also be common in Alzheimer's disease and related dementias (ADRD) clinical trial participants, potentially confounding the results of interventional trials that are designed to target a solitary pathophysiologic mechanism. Method: The University of Kentucky Alzheimer Disease Research Center autopsy database was screened for participants that had previously engaged in therapeutic interventional trials for Alzheimer's disease, vascular cognitive impairment and dementia, and/or ADRD prevention trials from 2005 to present. Seventy‐five cases (out of a total n = 546) had engaged in clinical trials for the prevention or treatment of ADRD. Pathologic features studied included b‐amyloid, tau, a‐synuclein, TDP‐43, and cerebrovascular disease using conventional rating scales. Result: Autopsy cases for those that previously engaged in clinical trials did not differ significantly from those that were trial‐naïve in respect to demographic, genetic (ApoE), or clinical characteristics with the exception of CDR global scores that were lower for past trial participants (p<0.05). Comorbid pathologies were common across study types with a mean of 3 pathologic features/participant, 18% with quadruple misfolded proteinopathy (QMP; Ab, tau, a‐synuclein, & TDP43), and only 34% of MCI/AD trial participants demonstrating a "pure" disease state that was targeted by the study intervention. Conclusion: In our study, approximately 2 out of 3 ADRD trial participants had comorbid mixed pathologic features. Understanding the heterogeneity of pathologies seen in clinical trial participants may allow improved I/E criteria based on clinical features and the rational use of antemortem biomarkers to stratify the likelihood of mixed comorbid pathology that may be unwanted or may be the target for future interventional strategies. Such insights may also enable improved power analyses and statistical designs that may be able to adjust for the confounds of such mixed pathologic disease states that are common in ADRD clinical trials.